Respostas
respondido por:
12
2(x+1):3-3(x+2):4=(x+1):6
primeiro tira-se o mmc entre 3, 4 e 6
dai temos
8(x+1)/12-9(x+2)/12=2(x+1)/12
eliminado o denominador já que igualamos os 2 lados temos
8(x+1)-9(x+2)=2(x+1)
8x+8-9x-18=2x+2
8x-9x-2x=2-8+18
-3x=12
x=12/-3
x=-4
a raiz portanto é -4
primeiro tira-se o mmc entre 3, 4 e 6
dai temos
8(x+1)/12-9(x+2)/12=2(x+1)/12
eliminado o denominador já que igualamos os 2 lados temos
8(x+1)-9(x+2)=2(x+1)
8x+8-9x-18=2x+2
8x-9x-2x=2-8+18
-3x=12
x=12/-3
x=-4
a raiz portanto é -4
respondido por:
1
Resposta:
0,7
Explicação passo-a-passo:
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás